Literature Review: The Relationship Between Self-efficacy and Self-care in Patients with Type II Diabetes Mellitus - andriyani, nurul; Nisa, Raudhatun; Jumanah; Marliyanti; Mesquita, Felisbela; Suwanti (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Diabetes mellitus is a chronic disease that requires continuous management through optimal self-care behaviors. Successful self-care is influenced by various factors, one of which is self-efficacy, which is an individual's belief in their ability to manage their disease and take necessary actions. Self-efficacy plays a crucial role in increasing patient motivation, compliance, and consistency in activities such as diet management, physical activity, blood glucose monitoring, and adherence to medication. Therefore, studying the relationship between self-efficacy and self-care is crucial in efforts to improve the quality of diabetes mellitus management. This literature review aims to analyze the relationship between self-efficacy and self-care in diabetes mellitus patients based on the results of a literature review of various recent studies. This literature review employed a literature review method. A systematic search was conducted using a computer search using the Google Scholar database for articles published between 2021 and 2025. Only articles with a quantitative design and full text were included in this analysis. Key data were searched using the PICO (Population Intervention Compare Outcome) technique. The analysis was conducted by comparing research results and identifying consistent findings related to the relationship between the two variables. Result f this study was based on 20 articles reviewed, eight matched the topic of this literature review. All eight articles analyzed demonstrated a significant relationship between self-efficacy and self-care in patients with diabetes mellitus. Reported significance values ranged from p=0.000 to p=0.017, indicating a statistically significant relationship. Furthermore, several studies have found that self-efficacy is associated with glycemic control and patient well-being, reflecting successful self-care practices. One study even reported a correlation coefficient of r=0.693, indicating a strong and positive relationship between the two variables. This finding indicates that the higher a patient's self-efficacy, the better their self-care skills. Conclusion of this study was self-efficacy plays a significant role as a predictor in improving self-care behavior in patients with diabetes mellitus. Therefore, interventions that focus on increasing self-efficacy, such as health education, social support, and counseling, are needed to improve patient compliance in carrying out self-care and achieving optimal clinical outcomes.